2011
DOI: 10.1093/occmed/kqq196
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between risk factors and musculoskeletal disorders among classical musicians

Abstract: The biomechanical risk factors that predict PRMD are mainly associated with the upper limbs. A high association between PRMD and clinical observation emphasizes the need for further investigation of these risk factors and to study possible implementations in order to define 'prevention strategies' for musical routines and patterns, as used by classical musicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(152 citation statements)
references
References 23 publications
7
131
0
14
Order By: Relevance
“…A significant number of musicians (83%) acknowledged the presence of pain within the six months prior to the study. This percentage is similar to those reported elsewhere (Kaufman-Cohen & Ratzon, 2011;Leaver et al, 2011). These similarities in prevalence rates seem to exist despite the difference in employment status: music students (current study) versus professional musicians (Kaufman-Cohen & Ratzon, 2011; Leaver et al, 2011).…”
Section: Regression Analysessupporting
confidence: 88%
“…A significant number of musicians (83%) acknowledged the presence of pain within the six months prior to the study. This percentage is similar to those reported elsewhere (Kaufman-Cohen & Ratzon, 2011;Leaver et al, 2011). These similarities in prevalence rates seem to exist despite the difference in employment status: music students (current study) versus professional musicians (Kaufman-Cohen & Ratzon, 2011; Leaver et al, 2011).…”
Section: Regression Analysessupporting
confidence: 88%
“…These reviews look at risk factors, professional consequences, and various approaches to prevention and treatment with regard to physical problems (Chan & Ackermann, 2014;Chan, Driscoll, & Ackermann, 2013;Kaufman-Cohen & Ratzon, 2011;Molsberger & Molsberger, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some more optimistic results were presented by Papandreou et al [17], who identified musculoskeletal problems in 43% of the analyzed percussion players, aged 20-60 years. It should be emphasized that majority of the studies which have been conducted among instrumentalists concern adults and orchestral classical musicians [10,[18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%